2008
DOI: 10.1021/ef800175e
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Production of Soybean Biodiesel in Supercritical Ethanol−Water Mixtures

Abstract: The reaction efficiency of soybean oil transesterification in supercritical ethanol in a continuous catalyst-free process was investigated under different water concentrations. Experiments were performed at 350 °C and 20 MPa, with an oil/ethanol ratio of 1:40. A fatty acid ethyl ester content of 77.5% was obtained at a flow rate of 1.5 mL/min in a water-free system, while the maximum concentration of ethyl esters reached for a water content of 10 wt % was 68.1% at a flow rate of 1.0 mL/min. Decomposition and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
55
0
8

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(76 citation statements)
references
References 17 publications
6
55
0
8
Order By: Relevance
“…The magnitude of the main effects (A, B, C and D) in Equation (2) demonstrated that the operating pressure (B) has the lowest influence on the % (w/w) FAEE content, which agreed well with both the results in the preliminary part of this study (Section 3.1) and those previously reported in the literature in a catalyst-free system [7,22]. In the catalyst-free transesterification under SCA, the temperature has been reported to be the most important factor determining the completeness of the reaction [23][24][25], whereas, in this study, its effect was reduced to be equal to that of the alcohol/oil molar ratio and the total mass flow rate.…”
Section: The Optimization Studysupporting
confidence: 90%
See 1 more Smart Citation
“…The magnitude of the main effects (A, B, C and D) in Equation (2) demonstrated that the operating pressure (B) has the lowest influence on the % (w/w) FAEE content, which agreed well with both the results in the preliminary part of this study (Section 3.1) and those previously reported in the literature in a catalyst-free system [7,22]. In the catalyst-free transesterification under SCA, the temperature has been reported to be the most important factor determining the completeness of the reaction [23][24][25], whereas, in this study, its effect was reduced to be equal to that of the alcohol/oil molar ratio and the total mass flow rate.…”
Section: The Optimization Studysupporting
confidence: 90%
“…According to the production performance, the conventional homogeneous catalytic process cannot directly use high water and/or free fatty acids containing feedstocks but the SCE process is capable [7,22]. Even though the conventional process operates under atmospheric pressure, it generates a significant amount of waste and requires a long production time because the product washing step.…”
Section: Fuel Properties Analysismentioning
confidence: 99%
“…In order to evaluate the existence of thermal decompostion in the soybean oil transesterification with supercritical methanol, Olivares-Carrillo and Quesada-Medina (2011b) reported the evolution of the molar ratio between methyl linoleate and methyl palmitate (the main unsaturated and saturated FAMEs generated, respectively); the results showed that the molar ratio between these FAMEs decreased with the reaction time at 573 K/26 MPa and above: the higher the temperature, the lower the molar ratio. Vieitez et al (2008) showed that the trans isomer content increases with increasing reaction temperature and residence time for soybean oil ethanolysis under supercritical conditions. Kasim et al (2009) reported that the percentage of trans isomers can reach levels up to 16% under certain reaction conditions (30 MPa, 573 K) for the transesterification of rice bran oil in supercritical methanol.…”
Section: Decomposition Of Fatty Acidsmentioning
confidence: 99%
“…Kasim et al (2009) reported that the percentage of trans isomers can reach levels up to 16% under certain reaction conditions (30 MPa, 573 K) for the transesterification of rice bran oil in supercritical methanol. Vieitez et al (2008) utilized the term "decomposition" of fatty acids to refer to the decrease in their percentage due to the formation of other compounds (not necessarily implying that they have decomposed but have suffered some type of alteration). Using this definition, this research group reported at 623 K, 20 MPa, oil to ethanol molar ratio of 1:40 and 42 minutes of residence time ~62.0 wt% (Vieitez et al, 2009), 73 wt% (Vieitez et al, 2011), ~8.0 wt% (Vieitez et al, 2012) and ~16.0 wt% (Vieitez et al, 2012) for reactions with soybean oil, castor oil, rice bran oil and high oleic sunflower oil, respectively.…”
Section: Decomposition Of Fatty Acidsmentioning
confidence: 99%
“…At the same time, the effect of using co-solvents to reduce the viscosity of vegetable oils was successfully investigated (Sawangkeaw et al, 2007). Supercritical transesterification in ethanol was studied in a continuous reactor in 2008 (Vieitez et al, 2008). In 2009, carbon dioxide was applied to supercritical transesterification with ethanol to reduce the operating conditions (Bertoldi et al, 2009).…”
Section: The Chronological Development Of Supercritical Transesterifimentioning
confidence: 99%